Fluidized bed pyrolysis of distilled spirits lees for adapting to its circulating fluidized bed decoupling combustion - Yao, C.; Dong, Li; Wang, Y.; Yu, J.; Li, Q.; Xu, G.; Gao, S.; Yi, B.; Yang, J. (Elsevier, 2011)
Distilled spirits Lees, rich in cellulose, water and N element, are difficult to burn efficiently and cleanly in grate chain stock boiler. The circulating fluidized bed decoupling combustion (CFBDC) was therefore proposed to burn the distilled spirits lees efficiently and with low-NOx emission. The pyrolysis behavior of the distilled spirits lees was investigated in a fluidized bed reactor for optimizing the pyrolysis conditions of the pyrolyzer in CFBDC. The results showed that the distilled spirits lees began to devolatize at 250 °C and at 350-450 °C the tar yield reached its maximum of about 16.3 wt.% (dry base). The chemical oxygen demand (COD) value of the condensed liquid reached its maximum of about 50,000 mg/L at 450 °C. With raising temperature the pyrolysis gas tended to contain more CO and H 2 and less CO 2 . The functional groups H-O, aliphatic C-H, aromatic ring, C=O and C-O were all presented in the char generated at low-temperatures, while only the C-O group was identified for the char from the pyrolysis at 650 °C. The article suggested that the pyrolysis for the CFBDC was better around 500 °C so that certain volatiles could remain in the char to sustain stable combustion. © 2011 Elsevier B.V. All rights reserved.